Importance of International Accreditation for Global Recognition for Higher Education - Adiatma, Tini; Nopriawan MAHRIADI; Mega SUTEKI (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
Education is a gate to improving human resource quality in a country. It must be managed to achieve that target including higher education. Higher education that is well-managed can contribute to national development. Higher education should not be afraid of international accreditation or certification, because it can build their reputation and also the students’ reputation. This research aims to explain the importance of international recognition in higher education institutions. This research was conducted by studying literature about external quality assurance related to increasing international recognition in higher education. The advantages of international accreditation are to improve competitiveness. Higher education needs to prepare their institution for international accreditation to get international recognition, improve motivation to create a quality culture, establish the institution or study program, improve competitiveness, and measure organizational performance. International accreditation also being part of the institutional responsibility toward the stakeholder. International accreditation in higher education is a long target for most Indonesian higher education.